EFEKTIVITAS PENERAPAN STRATEGI INTERACTIVE INSTRUCTION DALAM MININGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DISEKOLAH MENEGAH PERTAMA NEGERI 2 PALENGAAN PAMEKASAN - Safira, Ida; Halik, Abd (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2024)
The effectiveness of implementing the learning strategy interactive instruction strategy in improving student learning achievement in the PAI subject was carried out to get an overview of student learning outcomes at the school. There are two main problems in this research, namely the effectiveness of using interactive instruction learning strategies in improving student learning achievement. The research method used in the research is a qualitative approach, the data sources are principals, PAI teachers, and students. The data analysis is by reducing the data, presenting the data, and verifying the data in the conclusion. The results of the research show that, 1) this strategy is effective because, with this learning strategy, students can express their opinions freely so that the classroom situation becomes effective and conducive, in participating in Islamic religious and moral education learning with the use of interactive instruction strategies students do not feel bored and more can understand the theory presented by the teacher. 2) The inhibiting factors in using interactive instruction learning strategies are the lack of seriousness in learning from students and the lack of student awareness of the importance of formal education and students' physical fatigue. The implications of this research are: 1) Development of more interactive teaching methods, 2) Increased student participation, 3) Development of social and communication skills, 4) Increased understanding of religious concepts, 5) Use of technology in learning.